Konstruktivisme Bruno Latour dan Implikasinya Terhadap Ide Keagenan Sosiologi - Robet, Robertus; Rozak R, U Abdul (UI Scholars Hub, 2023)
Abstract Latour removes the boundaries between natural sciences and humanities. Science for Latour is cultural practise, at the same time in every cultural practice, nature and objects are also actively involved. With that, Latour's constructivism encourages the emergence of non-human actors as drivers of the societal changes. With that he provoked sociology to expand its subject matter. The Social in sociology must be seen as an association involving human and non-human actors.